Pengaturan Hukum Terkait Penggunaan Telepon pada Penagihan Peer to Peer Lending - Debrina Rahmawati (Pusat Riset dan Inovasi Nasional, 2024)
Peer to peer lending (P2PL) is an online-based money lending platform. P2PL billing is very diverse even though it has been regulated in several regulations in Indonesia but still requires continuous study. The objectives of this study are (1) To find out the reasons for the need for more detailed legal rules related to debt collection procedures in P2PL and (2) To find out the future legal rules regarding P2PL debt collection procedures that have not been regulated in Indonesian laws and regulations. This research uses normative juridical research using statutory, conceptual and comparative legal approaches. The result of this research is the reason for the need for more detailed legal arrangements related to debt collection procedures in P2PL is to achieve justice in the form of balance for the parties involved in P2PL and the detailing of billing arrangements by telephone means which are explicitly stated in the legislation by categorizing continuous telephone ringing and conducting telephone conversations repeatedly with the intention of disturbing, abusing, or harassing someone at the intended number in the category of violence and the obligation to disclose the identity of P2PL debt collectors in every collection in any form.